A retrospective cohort analysis of people living with HIV/AIDS enrolled in HIV care at a reference center in Antananarivo, Madagascar - Raberahona, Mihaja; Rakotomalala, Rado; Andriananja, Volatiana; Andriamamonjisoa, Johary; Rakotomijoro, Etienne; Andrianasolo, Radonirina Lazasoa; Rakotoarivelo, Rivonirina Andry; Randria, Mamy Jean de Dieu (Frontiers in Public Health, 2024)
The impact of “Treat all” policy on the individual and in terms of public health is closely related to early diagnosis and retention in care. Patient-level data are scarce in Madagascar. In this study, we aimed to describe the profile of a cohort of newly diagnosed people living with HIV/AIDS (PLHIV), to identify their outcome, and to assess factors associated with attrition from care and advanced HIV disease (AHD) at presentation. We conducted a retrospective cohort study in PLHIV aged ≥15 newly diagnosed at the University Hospital Joseph Raseta Befelatanana Antananarivo from 01/01/2010 to 31/12/2016. A total of 490 PLHIV were included in the cohort analysis. A total of 67.1% were male. The median age (interquartile range) at enrollment in care was 29 years (24-38). Overall, 36.1% of PLHIV were diagnosed with AHD at baseline. The proportion of patients with WHO stage IV at baseline significantly increased from 3.3% in 2010 to 31% in 2016 (p=0.001 for trend). The probability of retention in care after the diagnosis at 12 months, 24 months and 36 months was 71.8%, 65.5% and 61.3% respectively. Age≥40 years (aHR:1.55; 95%CI:1.05-2.29; p=0.026), low level of education (aHR:1.62; 95%CI:1.11-2.36; p=0,013), unspecified level of education (aHR:2.18; 95%CI:1.37-3.47; p=0.001) and unemployment (aHR:1.52; 95%CI:1.07-2.16; p=0.019) were independently associated with attrition from care. Factors associated with AHD at baseline were age≥40 (aOR: 2.77; 95%CI: 1.38-5.57, p=0.004), unspecified level of education (aOR:3.80; 95% CI: 1.58-9.16, p=0.003) and presence of clinical symptoms at baseline (aOR:23.81; 95% CI: 10.7-52.98; p<0.001). Sex workers are independently less likely to have an AHD at presentation (aOR: 0.23; 95%CI: 0.05-0.96, p=0.044). Sociodemographic determinants influenced retention in care more than clinical factors. The presence of clinical symptoms and sociodemographic determinants were the major factors associated with AHD at baseline.